1992
DOI: 10.1007/bf00318689
|View full text |Cite
|
Sign up to set email alerts
|

Salinity tolerance and structure of external and internal gills in tadpoles of the crab-eating frog, Rana cancrivora

Abstract: Salinity tolerance and histology of gills were studied in Rana cancrivora larvae. The tadpoles at the external gill stages (W stages 21-22) were able to survive in media containing up to 40% seawater, but died in water of higher salinity. Their external gills appear to have no critical role in adaptation to seawater. However, advanced tadpoles with internal gills (T-K stages I-XVIII) were able to tolerate 50% or higher seawater. In the internal gills, there are numerous mitochondria-rich cells (MR cells) scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Tadpoles experiencing low salinity in early development (before Gosner stage 38) had much higher survival rates (100%) than tadpoles exposed to high salinity during the same period, even if they were later switched to low salinity. Gills are the main organs responsible for ion and water balance in tadpoles (Dietz and Alvarado 1974;Uchiyama and Yoshizawa 1992;Ultsch et al 1999), and tadpoles may lack sufficient salt-excreting ability to cope with high osmotic stress until internal gills develop (Chinathamby et al 2006). Uchiyama and Yoshizawa (1992) suggested that the euryhaline tadpoles of Fejervarya cancrivora (Rana cancrivora) tolerated higher salinity once they had internal gills than those still relying on external ones because the former are more abundant in mitochondria-rich cells (MR cells), thought key in ion excretion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Tadpoles experiencing low salinity in early development (before Gosner stage 38) had much higher survival rates (100%) than tadpoles exposed to high salinity during the same period, even if they were later switched to low salinity. Gills are the main organs responsible for ion and water balance in tadpoles (Dietz and Alvarado 1974;Uchiyama and Yoshizawa 1992;Ultsch et al 1999), and tadpoles may lack sufficient salt-excreting ability to cope with high osmotic stress until internal gills develop (Chinathamby et al 2006). Uchiyama and Yoshizawa (1992) suggested that the euryhaline tadpoles of Fejervarya cancrivora (Rana cancrivora) tolerated higher salinity once they had internal gills than those still relying on external ones because the former are more abundant in mitochondria-rich cells (MR cells), thought key in ion excretion.…”
Section: Discussionmentioning
confidence: 98%
“…Gills are the main organs responsible for ion and water balance in tadpoles (Dietz and Alvarado 1974;Uchiyama and Yoshizawa 1992;Ultsch et al 1999), and tadpoles may lack sufficient salt-excreting ability to cope with high osmotic stress until internal gills develop (Chinathamby et al 2006). Uchiyama and Yoshizawa (1992) suggested that the euryhaline tadpoles of Fejervarya cancrivora (Rana cancrivora) tolerated higher salinity once they had internal gills than those still relying on external ones because the former are more abundant in mitochondria-rich cells (MR cells), thought key in ion excretion. Concordantly, MR cells only appeared in Rana dalmatina tadpoles once internal gills had developed, but were absent in their external gills (Brunelli et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…The MRC has been noted in the epithelium of the external gills of R. cancrivora tadpoles, adapted to 10% seawater (Uchiyama and Yoshizawa 1992), even if in a rather reduced number; in the same paper the authors reported the presence of a few MRCs even in the epidermis of the early larvae of R. cancrivora. In the experiments conducted by the same authors on tadpoles acclimatized to different concentrations of seawater, the tadpoles at external gill stages showed a lower tolerance compared to tadpoles of internal gill stages, managing to survive only until a concentration equal to 40% of seawater in comparison to 100% for tadpoles with internal gills.…”
Section: Transient Gillsmentioning
confidence: 89%
“…The respiratory apparatus of Anura has been the subject of different studies relating to anatomy and gill ultrastructure in different species: Discoglossus pictus Otth, 1837 (Hourdry 1974), Rana cancrivora Gravenhorst, 1829 (Uchiyama and Yoshizawa 1992;Uchiyama et al 1990), Litoria ewingii Dumeril &Bibron, 1841 (McIndoe andSmith 1984). Others have studied gill apparatus in connection with blood circulation (De Saint-Aubain 1981) or with regard to different aspects which involve pharyngeal organs (Seale et al 1982;Viertel 1982Viertel , 1985aWassersug 1972Wassersug , 1976Wassersug , 1984; moreover larval oral cavity morphology has also been used in studies of evolutionary relationships (Wassersug 1980;Wassersug and Heyer 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation